Enhanced hyaluronic acid production from Priestia flexa N7 isolates - Dinh Giap Vu; Thi Cam van Do; Linh Mai Dau Thi; Danh Phong Dang; Bich Ngoc Thi Khuat; Oanh Kim Hoang Thi; Thu Minh Do; Thi Dung Ha; The Vinh Mac; Phuong Dai Nguyen Nguyen (Biomedical and Biotechnology Research Journal, 2024)
Background: Hyaluronic acid (HA) is a gel-like substance made up of glucuronic acid and N-acetylglucosamine units, capable of absorbing and retaining water, present in hydrated gel form across human and animal tissues. It aids in joint lubrication and moisture retention and acts as a cushion for shock absorption. HA has unique biological properties, promoting fibroblast cell growth, aiding wound healing, and exhibiting low solubility and viscosity, making it an organic ingredient in tissue culture techniques. It is utilized in eye drops and skin ointments and plays a vital role in the extracellular matrix, rendering it invaluable in medical and cosmetic applications, such as treating osteoarthritis and enhancing skin wound recovery. Methods: The methods employed in this study involve isolating microorganisms, screening bacterial strains capable of synthesizing HA, identifying bacteria using molecular biological methods, and researching optimal conditions to select bacterial strains that produce the highest HA concentrations. Results: In this study, strain Priestia flexa N7 was studied for suitable conditions for HA biosynthesis. Bacterial strains were fermented for 48 h on medium containing the following ingredients: glucose (60 g/L); yeast extract (5.0 g/L); peptone (20 g/L); K2HPO4 (2.0 g/L); Na2HPO4 (1.0 g/L); NaCl (2.0 g/L); FeSO4 (1.0 g/l); sodium glutamate (9.0 g/L); and MgSO4.7H2O (2.0 g/L) and pH 8.0 at 37°C under the condition of continuous shaking at 150 rpm. The maximum HA production achieved was 1105 mg/L. Conclusions: The mentioned bacterial strain exhibits significant potential for HA synthesis and is extensively employed in producing items across the health care, medical, food, and cosmetic industries. These findings revealed the most effective HA acid manufacturing strategy for achieving maximum output.